The Effect of Manager Gender and Performance Feedback: Experimental Evidence from India - Martin Abel; Daniel Buchman (Institute of Labor Economics (IZA), 2020)
We hire 1,800 Indian gig economy workers for a real-effort transcription task and randomize the gender of the (fictitious) manager as well as the delivery of performance feedback. We find that negative feedback (i.e. criticism) leads to moderate deterioration in worker attitudes, but it increases effort provision in both mandatory and voluntary tasks. By contrast, praise affects neither attitudes nor effort provision. Importantly, feedback effects do not vary between workers assigned to female and male managers. Consistent with this finding, there is no evidence for attention discrimination towards female managers, implicit gender bias, or gendered expectations among workers. By contrast, Abel (2019) employs the same research design in the U.S. and finds substantial gender discrimination and no effect of feedback on effort. This highlights that the effects of feedback and manager gender vary across different contexts.
Keywords: J50; J70; 330; India; gender discrimination; gig economy; feedback